The impacts of removing fossil fuel subsidies and increasing carbon tax in Ireland - Kelly C. De Bruin; Eoin Monaghan; Aykut Mert Yaku (The Economic and Social Research Institute (ESRI), 2019)
This research finds that simultaneously removing seven fossil fuel subsidies would have a modest adverse effect on real GDP and household income. However, it would have a sizeable impact on reducing economy-wide emissions. Increasing the carbon tax at the same time as removing the subsidies would slightly increase the adverse economic impact but lead to a more substantial decline in emissions. The results are based on research using the ESRI's Environment, Energy and Economy (I3E) model for Ireland. The research was funded by the Department of Communications, Climate Action and Environment.
Keywords: 330